2020
DOI: 10.2166/wrd.2020.009
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenotrophic denitrification for treating nitrate contaminated without/with reactive black 5 dye

Abstract: NO3-N and dye colors discharged from textile wastewater pose environmental problems in Thailand. This study aimed to observe the nitrogen removal rate (NRR) with and without RB-5 color contamination via hydrogenotrophic denitrification (HD) processing, which uses H2 gas as electron donor to reduce NO3-N and NO2-N; comparing with bioreactors treatment to evaluate systems that can simultaneously remove NO3-N and dye color. Five reactors under different operation and gas supply conditions were set-up under HRT of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The effluent of the nitrification system contains high DO as previously reported [20], which is the same as the influent of the simplified HD reactor. However, the HD system can be inhibited by high DO concentrations [47,48], and Singhopon et al has suggested that the DO value should be between 0.5 and 0.8 mg-O 2 /L to improve NRR [48]. In the present study, supplying H 2 gas into the reactor was instrumental in maintaining the preferred range of DO concentrations for HD.…”
Section: Ambient Condition and Changes In Operational Parametersmentioning
confidence: 67%
“…The effluent of the nitrification system contains high DO as previously reported [20], which is the same as the influent of the simplified HD reactor. However, the HD system can be inhibited by high DO concentrations [47,48], and Singhopon et al has suggested that the DO value should be between 0.5 and 0.8 mg-O 2 /L to improve NRR [48]. In the present study, supplying H 2 gas into the reactor was instrumental in maintaining the preferred range of DO concentrations for HD.…”
Section: Ambient Condition and Changes In Operational Parametersmentioning
confidence: 67%
“…Considering that the functional bacteria require an adaptation time in order to function properly under a high amount of toxic contamination, nitrogen removal was enhanced when the RB-5 dye was added. A previous study revealed that NO3-N and NO2-N could be removed when the environment is contaminated with high RB-5 concentrations, and NRE was greater when RB-5 was added to the system [21].…”
Section: Effect Of Initial Rb-5 Dye Concentration On Nrementioning
confidence: 97%
“…Synthetic textile wastewater was prepared based on the quality of textile wastewater in Thailand, which has a composition as previously described: 486 mg NaNO 3 /L (80 mg NO 3 -N/L), 110 mg KH 2 PO 4 /L, 1000 mg NaHCO 3 /L, 21 mg CaCl 2 /L, 38 mg MgSO 4 •7H 2 O/L, and 1.0 mL of trace elements (I) and (II) [21,22] [23]. Furthermore, in this study, the concentrations of the azo dye were varied (10, 15, 30, and 60 mg/L) depending on the operating conditions of each phase, as described in Table 1.…”
Section: Synthetic Textile Wastewatermentioning
confidence: 99%
See 2 more Smart Citations